Assessing Levels Along with Risks Due To Fluoride Toxicity in Tohana Block of Fatehabad District, Haryana, India - Kumari, Seema; Saini, Alka; Dhankhar, Harsh (International Journal of Applied Sciences and Biotechnology, 2025)
The purpose of the present research was to assess the fluoride concentration of the surface and groundwater in the Tohana block of Fatehabad district, Haryana. Groundwater serves as the area's main supply of drinking water. 53 samples were collected each from surface (ponds, rivers) and groundwater (tubewells, handpumps and wells) and were examined for fluoride concentration using ion selective electrode. Fluoride concentration ranged from 0.02 mg/l (Lalodha, Rainwali) to 1.91 mg/l (Nanheri) in Tohana block, Fatehabad District in Haryana. 43 villages (out of 53 villages/Town) of Fatehabad district had fluoride levels that were below the WHO's highest admissible limit of 1.5 mg/l; however, Fluoride levels in 10 (out of 53 villages/towns) exceeded the permissible level; making them inadequate for drinking. The principal origins of fluoride in groundwater are assumed to be the abundance of fluoride-bearing minerals in the host rock, along with chemical characteristics like dissociation, dissolution and decomposition, in addition to their interaction with water. Int. J. Appl. Sci. Biotechnol. Vol 13(3): 123-129.